FACTORS RELATED TO SELECTION OF LABOR AIDING IN MATERNITY MOTHERS - suchi avnalurini Sharief (Alliance oh Health Activists (AloHA), 2018)
The focus on reducing MMR is carried out on activities that include three messages in the MPS program, namely that each delivery is assisted by trained health workers, each obstetric and neonatal complications receive adequate services and every woman of childbearing age has access to prevention of unwanted pregnancy and management of miscarriage complications. The higher the coverage of childbirth by health workers, the lower the risk of death, therefore the goal of health development, one of which is to significantly increase the number of pregnant women who get examined and give birth assisted by health workers. The purpose of this study was to determine the relationship of education, employment, family support, affordability of access to health facilities (transportation), socio-cultural relations with the selection of birth attendants in the Lede District Health Center Work Area. Lede Kab. Taliabu Island, North Maluku. This type of research is an observational study with a cross-sectional study approach, using a total sampling that is all mothers giving birth in the Lede District Health Center Work Area. Lede. Regency. North Maluku Taliabu Island from January to June 2018 as many as 61 people. The results of this study indicate that there is a relationship between education and the selection of birth attendants obtained P-value = 0,000